Optimization modeling to support renewables integration in power systems - Pereira, Sérgio Lima Barroso (2016)
This study focuses on the problem of generation expansion planning and the integration of an increasing share of renewable energy sources (RES) technologies in the power grid. A survey of papers addressing the use of optimization models for electricity generation planning is presented. From this, an electricity planning model able to integrate thermal and RES power plants was proposed. An analysis of different electricity scenarios for a mixed hydro-thermal-wind power system is presented using the proposed mixed integer optimization model. The results show the importance of these tools to support the strategic energy policy decision making under different regulatory or political scenarios. The expected impacts in terms of costs and CO 2 emissions are evaluated for a 10 year planning period, and a set of optimal scenarios is analyzed. The use of the model to obtain and characterize close to optimal scenarios is shown to be strategically useful. In particular the impact of different wind power scenarios is addressed, demonstrating the relevance of assessing other possible strategies that, despite not being original Pareto solutions, may be worth considering by the decision makers.